WHY WE NEED RELIGION TO SOLVE THE WORLD FOOD CRISIS. Issue 4 (18th November 2014) - Whitney Sanford, A.
Abstract Scholars and practitioners addressing the global food crisis have rarely incorporated perspectives from the world's religious traditions. This lacuna appears in multiple dimensions: until recently, environmentalists have tended to ignore food and agriculture; food justice advocates have focused on food quantities, rather than its method of production; and few scholars of religion have considered agriculture. Faith‐based perspectives typically emphasize the dignity and sanctity of creation and offer holistic frameworks that integrate equity, economic, and environmental concerns, often called the three legs of sustainability. Faith‐based perspectives can provide new paradigms through which to assess food, consumption, and production and the attendant social relations; assess our scientific, economic, and social approaches; and acknowledge the moral and religious dimensions of the world food crisis.